2015
DOI: 10.1016/j.forsciint.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Fatal poisoning in drug addicts in the Nordic countries in 2012

Abstract: This report is a follow-up to a study on fatal poisoning in drug addicts conducted in 2012 by a Nordic working group. Here we analyse data from the five Nordic countries: Denmark, Finland, Iceland, Norway and Sweden. Data on sex, number of deaths, places of death, age, main intoxicants and other drugs detected in the blood were recorded. National data are presented and compared between the Nordic countries and with data from similar studies conducted in 1991, 1997, 2002 and 2007. The death rates (number of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 17 publications
(3 reference statements)
9
71
0
2
Order By: Relevance
“…GHB-related fatalities have been reported primarily from Western countries, such as the USA, Canada, Australasia, and Europe (Caldicott et al, 2004;EMCDDA, 2008;Simonsen et al, 2015;Zvosec et al, 2011). This measure is often used as part of a range of indicators/parameters in national and international risk assessments of substances of concern (EMCDDA, 1999;Nutt et al, 2007;van Amsterdam et al, 2012) and provides "signals of emerging harms" (EMCDDA, 2014:8).…”
Section: Fatalitiesmentioning
confidence: 99%
“…GHB-related fatalities have been reported primarily from Western countries, such as the USA, Canada, Australasia, and Europe (Caldicott et al, 2004;EMCDDA, 2008;Simonsen et al, 2015;Zvosec et al, 2011). This measure is often used as part of a range of indicators/parameters in national and international risk assessments of substances of concern (EMCDDA, 1999;Nutt et al, 2007;van Amsterdam et al, 2012) and provides "signals of emerging harms" (EMCDDA, 2014:8).…”
Section: Fatalitiesmentioning
confidence: 99%
“…Various studies have been conducted to assess the abuse potential of tramadol, extending from pre-clinical receptor binding studies, studies in substance abusers (74,183), and postmarketing surveillance (184). These have shown that tramadol may induce physical dependence and withdrawal reactions, and is implicated in misuse, abuse and diversion (143), as well as intoxications, emergency department visits (185), and drug-related deaths (186,187). Yet, the addictive properties of tramadol are considered to be low (188)(189)(190).…”
Section: Tramadolmentioning
confidence: 99%
“…In Sweden, tramadol is the prescription drug most commonly encountered on the illicit market (138) and one of the most prevalent prescription drugs used by subjects deceased from traffic accidents (193), as in some other countries (187). However, whereas the occurrence of misuse and abuse of tramadol is now recognised, the global prevalence and the relevance of the problem for the patients on prescribed treatment is not fully known.…”
Section: Tramadolmentioning
confidence: 99%
See 1 more Smart Citation
“…A tendency of increase in its consumption patterns as reflected by the data of seizures of this substance (unodc, 2013). In addition, in some areas of Northern and Central Europe the consequences of its use are already beginning to suppose serious medical and social problems (Csáki et al, 2013;Simonsen et al, 2015). Therefore, our goal is to provide a brief explanation of mdpV's chemical properties and review the locomotor activating effects and addiction-like features of mdpV that have been assessed in preclinical studies, while comparing them with classic addictive drugs.…”
mentioning
confidence: 99%